Counterintuitive Role of Magnesium Salts as Effective Electrolyte Additives for High Voltage Lithium‐Ion Batteries. Issue 15 (6th May 2016) - Wagner, Ralf; Streipert, Benjamin; Kraft, Vadim; Reyes Jiménez, Antonia; Röser, Stephan; Kasnatscheew, Johannes; Gallus, Dennis Roman; Börner, Markus; Mayer, Christoph; Arlinghaus, Heinrich Franz; Korth, Martin; Amereller, Marius; et al.
Abstract : Further development of high voltage lithium‐ion batteries requires electrolyte formulations stable against oxidation or measures to generate a protective cathode/electrolyte interface (CEI) film. In the frame of this work, the actually counterintuitive concept of using metal ions as electrolyte additives to stabilize the CEI has proven to be successful. The addition of 1 wt% magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI)2 ) as electrolyte additive to a conventional LiPF6 /organic carbonate electrolyte suppresses the oxidative decomposition of the bulk electrolyte as displayed in improved capacity retention, increased Coulombic efficiencies, and reduced self‐discharge of LiNi1/3 Mn1/3 Co1/3 O2 (NMC111)/Li half cells charged to the elevated upper cutoff potential of 4.6 V versus Li/Li + at 20 °C. Moreover, the addition of Mg(TFSI)2 shows no adverse effect on the cycling performance of graphite anodes, as observed by good long‐term cycling results of NMC111/graphite full cells. Ex situ analysis via X‐ray photoelectron spectroscopy, scanning electron microscopy, time‐of‐flight secondary ion mass spectrometry, and electron energy loss spectroscopy of the harvested NMC111 electrodes after cycling indicate that the addition of Mg 2+ ions leads to the formation of a CEI layer as a result of an increased hydrolysis reaction of the PF6 – anion. Abstract : Magnesium salts are used as novel electrolyte additives to enable the application of LiNi1/3 Mn1/3 Co1/3 O2 cathodes at the elevated upper cutoff potential of 4.6 V versus Li/Li + without degradation of the active material or the conventional LiPF6 /carbonate‐based electrolyte. In case of the Mg‐based additive, the cathode/electrolyte interface is stabilized by the formation of oxygenated salt derived species (PF x O y − ).